Perbandingan Kriptography Klasik Caesar Cipher Dengan Kriptography Modern Aes Dalam Tingkat Keamanan Jaringan Komputer - Dimas Mayoni Aji Sasono; Muhlis Tahir; Fathricia Angel M. V.; Mar’atul Azizah; Luluk Fariska Utami; Nurul Septiana (Jurnal Informasi, Sains dan Teknologi, 2023)
Cryptography (cryptography) is the science and art of keeping messages safe. The sender of the message will encrypt it while the recipient of the message will decrypt it. The encryption and decryption process uses keywords that have been agreed upon by the sender and recipient of the message. To better understand the development of cryptography, this journal will introduce a comparison of classical cryptography and modern cryptography at the level of computer network security. The cryptography that will be compared is Caesar Cipher and AES. This study uses the method of literature review (library research), namely research based on expert opinion and the results of previous studies.